Relating new graduate nurse competence to frequency of use - Hengstberger-Sims, C.; Cowin, L.; Eagar, S.; Gregory, L.; Andrew, S.; Rolley, John Xavier (Royal College of Nursing Australia, 2008)
The healthcare workplace can be a stress-laden environment for new graduates and job performance indicators are an important sign of developing confidence and expertise that will lead to improved patient outcomes. What is not evident from nursing studies is whether new graduate nurse competencies relate to the frequency of their use. This study sought to determine the relationship between perceived nursing competence and self-assessed frequency of use by new graduate nurses. Three cohorts (n=116) of new graduate nurses undertaking year-long transition to graduate practice programs responded to a questionnaire that utilised the 2001 ANCI competencies and the Nurse Competency Scale and a Visual Analogue scale to self assess their perceived competence and relative frequency of use for specific competence items.Results indicate that a relationship exists between perceived competence and frequency of use and that research competency scores are substantially lower than all other categories of competency. Implications for education and practice indicate that assessment of nurse competency for the new graduate nurse should focus on the development of generic nursing competencies rather than current expectation of advanced and workplace specific nurse competencies.